2017
DOI: 10.1177/0049475517698869
|View full text |Cite
|
Sign up to set email alerts
|

Ameloblastoma resection with immediate rib reconstruction: addressing the problem of mandibular angle and central bone bulk

Abstract: Several methods are available to treat mandibular tumours. This case series demonstrates the feasibility of resection and immediate reconstruction with free rib graft in limited resource settings. Innovative technical modifications are described to handle the problem of reconstruction of the angle of the mandible and to provide increased bone bulk in the centre of the mandible. Early postoperative complications are few. Follow-up demonstrates good functional results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 8 publications
0
13
1
2
Order By: Relevance
“…5,1,4,6 En este caso se realizó la resección completa con márgenes de seguridad de las lesiones, más la colocación de una placa de reconstrucción a través de un abordaje extraoral, se decidió por un tratamiento agresivo debido a la alta tasa de recurrencia del ameloblastoma y del fibroma osificante, y a los 6 meses posterior a la cirugía no se evidenciaron recidivas. 7,4,6,8,5,14 Este es el primer caso reportado en la literatura en el cual se presenta de forma simultánea en la misma hemimandíbula un fibroma osificante y un ameloblastoma, esta combinación puede deberse a la casualidad como lo describieron Hosseini y…”
Section: Discussionunclassified
See 1 more Smart Citation
“…5,1,4,6 En este caso se realizó la resección completa con márgenes de seguridad de las lesiones, más la colocación de una placa de reconstrucción a través de un abordaje extraoral, se decidió por un tratamiento agresivo debido a la alta tasa de recurrencia del ameloblastoma y del fibroma osificante, y a los 6 meses posterior a la cirugía no se evidenciaron recidivas. 7,4,6,8,5,14 Este es el primer caso reportado en la literatura en el cual se presenta de forma simultánea en la misma hemimandíbula un fibroma osificante y un ameloblastoma, esta combinación puede deberse a la casualidad como lo describieron Hosseini y…”
Section: Discussionunclassified
“…El tratamiento del ameloblastoma puede ser un problema debido a su alta taza de recurrencia con tratamientos conservadores, pero también hay que tomar en cuenta las complicaciones de un tratamiento agresivo y las técnicas reconstructivas que se pueden utilizar. 7,4,6 El fibroma osificante (FO) fue descrito por primera vez en 1872 por Menzel en un paciente femenino de 35 años de edad, la cual presentó un tumor en la mandíbula. Desde entonces el (FO) ha sido reclasificado dentro de diferentes categorías.…”
Section: Introductionunclassified
“…The three changes in the classification of odontogenic keratocyst by WHO suggest that the peculiar characteristics of this lesion are of paramount importance for differential diagnosis and therefore, important to compose an adequate surgical treatment choice. 3,6,10,11 The KOC can manifest itself as unilocular or multilocular form. The unilocular form has similarities w it h t he unic yst ic a meloblastoma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, for these lesions there are different complexities to surgical management, sometimes there is a specific treatment. [9][10][11][12] Magnetic resonance imaging is a technique that has great ability to differentiate soft tissues Some studies, after confirming the lesions by anatomopathological examination, were directed to the purpose of performing a differential diagnosis of keratocysts through the use of magnetic resonance imaging. 8,[14][15][16][17] Thus, the aim of this study is to review studies that have applied magnetic resonance imaging as a tool for differentiating OKC from ameloblastomas.…”
Section: Introductionmentioning
confidence: 99%
“…15 However, there is a paucity of long-term studies that examine patient-reported function, determinants of quality of life, and complication rates to establish if this technique is indeed still a viable option in settings without access to microsurgery. [15][16][17][18][19] These data might help to promote the uptake of this method and improve the lives of patients with large ameloblastoma in LMICs.…”
Section: Introductionmentioning
confidence: 96%